Arsenic trioxide therapy predisposes to herpes zoster reactivation despite minimally myelosuppressive therapy. (July 2021) - Glass, Jacob L.; Derkach, Andriy; Hilden, Patrick; King, Amber; Seo, Susan K.; Ahr, Katya; Kishtagari, Ashwin; Levine, Ross L.; Tallman, Martin S.; Douer, Dan
Highlights: Acute promyelocytic leukemia is highly responsive to minimally myelosuppressive therapy with all-trans retinoic acid and arsenic trioxide. Arsenic trioxide increases the risk of herpes zoster infection. Acyclovir prophylaxis is recommended for all patients receiving arsenic trioxide. Abstract: Acute Promyelocytic Leukemia (APL) is a unique subtype of acute myeloid leukemia that is highly responsive to minimally myelosuppressive therapy with all-trans retinoic acid (ATRA) and arsenic trioxide (ATO). We and others have observed a higher than expected incidence of herpes zoster reactivation in APL patients treated with ATO. Memorial Sloan Kettering Cancer Center (MSKCC) has been using ATO since 1997 in all relapsed APL patients, and more recently has included it in our front-line APL regimens. Here we present a retrospective analysis of the factors contributing to herpes zoster reactivation among APL patients.